Response-related predictors of survival in CML - Hanfstein, Benjamin; Müller, Martin Christian; Hochhaus, Andreas (Annals of hematology, 2015)
The assessment of response to tyrosine kinase inhibitor (TKI) treatment in chronic myeloid leukemia (CML) does not only reflect tumor burden at a given time but has been shown to be linked to long-term survival outcomes as well. Therefore, the quantification of molecular or cytogenetic response as early as 3 months on treatment allows a prognostic stratification of a patient’s individual risk. With competing TKI regimens available, a timely switch of treatment can be considered if unfavorable outcome has to be expected due to early response failure. Numerous studies have demonstrated the association of long-term outcome with early response for first-line treatment with imatinib, with second-generation TKI and for second-line TKI treatment as well.
Gesehen am 13.11.2017